Mathematical reasoning and communication word problems with mathematical problem-solving orientation: A relation between the skills - Aljura, Ahmad Naufal; Retnawati, Heri; Dewanti, Septinda Rima; Kassymova, Gulzhaina Kuralbayevna; Sotlikova, Rimajon; Septiana, Atut Reni (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Developing students’ mathematical reasoning skills (MRS) and mathematical communication skills (MCS) is crucial, as both are foundational to effective mathematical problem-solving (MPS). Despite their theoretical interconnectedness, limited empirical evidence exists on how MRS and MCS relate to MPS, particularly in problem-based contexts. This study investigates the relationship between MRS and MCS within an MPS-oriented framework using a quantitative, descriptive correlational design. A modified mathematical word problem (MWP) essay test was administered to 117 students across two pilot classes. The test items were designed to elicit reasoning and communication processes associated with MPS. Psychometric analyses—including evidence of content validity (Aiken’s V), consequential validity, reliability indices (α and ω), and item-level metrics (discrimination and difficulty)—confirmed the instrument’s robustness. Factor analysis supported a unidimensional structure aligned with MPS. Correlational analyses revealed significant positive associations between MRS and MCS, meeting bivariate normality assumptions. Pearson’s r was 0.529 (95% CI: 0.261–0.722), Spearman’s ρ was 0.493 (95% CI: 0.215–0.697), and Kendall’s τ was 0.400 (95% CI: 0.101–0.632), indicating a strong relationship. These findings underscore the interdependence of reasoning and communication skills in the context of MPS. The study also offers a detailed analysis of student obstacles in solving MWPs, offering a nuanced understanding of cognitive and linguistic dimensions in MPS. Implications are discussed for researchers, policymakers, and educators, particularly in designing instructional interventions that strengthen MRS and MCS in support of MPS.